2003
DOI: 10.1146/annurev.biochem.72.121801.161809
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Approach to Mammalian Glycan Function

Abstract: The four essential building blocks of cells are proteins, nucleic acids, lipids, and glycans. Also referred to as carbohydrates, glycans are composed of saccharides that are typically linked to lipids and proteins in the secretory pathway. Glycans are highly abundant and diverse biopolymers, yet their functions have remained relatively obscure. This is changing with the advent of genetic reagents and techniques that in the past decade have uncovered many essential roles of specific glycan linkages in living or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
449
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(452 citation statements)
references
References 255 publications
2
449
0
1
Order By: Relevance
“…Diverse processes seem to depend on precise control of protein glycan "codes." Glycosyltransferase knockouts frequently cause strong developmental defects in mammals (Lowe and Marth, 2003;Angata et al, 2006), and altered protein glycosylation is frequently associated with malignant cancer (Sato and Furukawa, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse processes seem to depend on precise control of protein glycan "codes." Glycosyltransferase knockouts frequently cause strong developmental defects in mammals (Lowe and Marth, 2003;Angata et al, 2006), and altered protein glycosylation is frequently associated with malignant cancer (Sato and Furukawa, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation reactions are catalyzed by the glycosyltransferases, including N-acetylglucosaminyltransferase V (MGAT5), also known as GnT-V, which plays a regulatory role in the synthesis of complex N-glycans; this process is highly conserved in mammals [17,18]. It has been reported that an aberrant glycosylation induced by MGAT5 is associated with tumor malignant transformation, including tumor invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Processing of core glycans into the complex type is then achieved in the endoplasmic reticulum (ER) 4 and Golgi apparatus compartments (1). Protein-attached glycans have been shown to have a wide range of biological functions, most notably stabilization of protein structure and cellular trafficking (2).…”
mentioning
confidence: 99%